Selective catalytic reduction articles and systems

A copper-containing molecular sieve catalyst with optimized Cu+2 and Cu(OH)+1 ratios and T-O-T asymmetric stretching peaks enhances SCR catalyst stability and NOx conversion efficiency, addressing high temperature hydrothermal durability and low temperature performance challenges.

JP7603737B2Active Publication Date: 2024-12-20BASF MOBILE EMISSIONS CATALYSTS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023067456
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-03-20
Filing Date
2023-04-17
Publication Date
2024-12-20
Estimated Expiration
2038-03-20

AI Technical Summary

Technical Problem

Existing SCR catalysts face challenges in maintaining high temperature hydrothermal durability and low temperature NOx performance due to transient exhaust temperature fluctuations in diesel particulate filter regeneration, necessitating improvements in catalyst stability and activity.

Method used

A copper-containing molecular sieve catalyst with specific Cu+2 and Cu(OH)+1 ion-exchanged ratios and perturbed T-O-T asymmetric stretching vibrational peaks, along with a silica-to-alumina ratio of 5 to 35, is developed to enhance catalyst stability and NOx conversion efficiency.

Benefits of technology

The catalyst exhibits improved NOx conversion rates and hydrothermal stability, maintaining high performance even after aging at 800°C, with minimal peak area increase, thus addressing the durability issues in SCR processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603737000006
    Figure 0007603737000006
  • Figure 0007603737000007
    Figure 0007603737000007
  • Figure 0007603737000008
    Figure 0007603737000008
Patent Text Reader

Abstract

To provide a method capable of identifying useful copper-containing molecular sieve catalytic materials that can be expected to exhibit good NOx conversion activities and also be aging stable.SOLUTION: A copper-containing molecular sieve catalyst contains ion-exchanged copper as Cu+2 and Cu(OH)+1. A DRIFT spectroscopy of the catalyst exhibits perturbed T-O-T vibrational peaks corresponding to the Cu+2 and Cu(OH)+1. In the resultant spectra of the catalytic material, a ratio of the peak integration area for the Cu+2 to the peak integration area for the Cu(OH)+1 can be 1 or more. The copper-containing molecular sieve catalysts are aging stable such that the peak integration area percentage of the Cu+2 peak (area Cu+2 / (area Cu+2+ area Cu(OH)+1)) increases by 20% or less upon aging at 800°C for 16 hours in the presence of 10% H2O / air, compared to the fresh state.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to selective catalytic reduction (SCR) catalysts, catalyst articles, systems, and methods suitable for treating exhaust from internal combustion engines. [Background technology]

[0002] Molecular sieves such as zeolites are used in catalysis of certain chemical reactions, for example, the selective catalytic reduction (SCR) of nitrogen oxides with reducing agents such as ammonia, urea, or hydrocarbons. Zeolites are crystalline materials with fairly uniform pore sizes ranging from about 3 to about 25 angstroms in diameter, depending on the type of zeolite.

[0003] Catalysts used in SCR processes must be able to retain good catalytic activity over a wide range of temperatures found in practical applications, including hydrothermal conditions with temperatures ranging from about 150° C. to about 800° C. or higher. SCR catalysts encounter hydrothermal conditions, where water is a by-product of fuel combustion. High temperature hydrothermal conditions occur in exhaust applications, such as during the regeneration of diesel particulate filters (DPFs) or catalyzed soot filters (CSFs), components of exhaust gas treatment systems used to remove carbonaceous particles.

[0004] The SCR process converts nitrogen oxides (NOx) to nitrogen (N2) and water (H2O). Nitrogen oxides (NOx) may include N2O, NO, N2O3, NO2, N2O4, N2O5, or HNO3. Improved articles, systems, and processes for selectively converting NOx in the exhaust stream of an internal combustion engine to N2 would be desirable. Improvements in high temperature hydrothermal durability are needed due to short-term transients where exhaust temperatures may reach 750°C, 800°C, 850°C, or even 900°C. Of particular importance is an improvement in low temperature NOx performance, for example, at about 150°C to about 300°C after high temperature hydrothermal aging. Summary of the Invention [Means for solving the problem]

[0005] In some embodiments, the present disclosure provides: Fresh The catalyst contains ion-exchanged copper, and 50 at% (atomic percent) or more of the ion-exchanged copper is Cu. +2 The present invention provides a copper-containing molecular sieve catalyst comprising (Hereinafter, in this specification, the terms "new state" and "new sample" are replaced with "fresh state" and "fresh sample", respectively.) .

[0006] In a further embodiment, the present disclosure can provide a copper-containing molecular sieve catalyst having a silica-to-alumina ratio (SAR) of from about 5 to about 35, or from about 14 to about 28, and a Cu / Al atomic ratio of from about 0.20 to about 0.50.

[0007] In another embodiment, the present disclosure provides a catalyst in its fresh state that is characterized by a Cu +2 Perturbed TOT asymmetric stretching vibration peaks corresponding to the cation, and Cu(OH) +1 The perturbed TOT asymmetric stretching vibration peak corresponding to the cation, Cu +2 and Cu(OH) +1 Contains ion-exchanged copper as Cu +2 and Cu(OH) +1 A copper-containing molecular sieve catalyst can be provided, in which the ratio of the peak integrated areas for each of the peaks is 1 or greater.

[0008] In yet another embodiment, the present disclosure provides a fresh catalyst that is characterized by the presence of Cu in the DRIFT spectrum of the catalyst. +2 The asymmetric stretching vibration peak of TOT corresponding to Cu(OH) +1 The TOT asymmetric stretching vibration peak corresponds to Cu +2 and Cu(OH) +1 Contains ion-exchanged copper as Cu +2 The integrated peak area of ​​the TOT asymmetric stretching vibration peak corresponding to Cu +2 and Cu(OH) +1 The percentage of the total integrated area of ​​the TOT asymmetric stretching vibration peaks corresponding to both +2 / (Area Cu+ 2+Area Cu(OH) +1 )) can be increased by no more than 20%, no more than 15%, no more than 10%, or no more than 5% compared to the fresh state upon aging at 800° C. for 16 hours in the presence of 10% HO / air.

[0009] The present disclosure may also provide a catalytic article comprising a catalytic coating disposed on a substrate, the catalytic coating comprising one or more coating layers, at least one coating layer being a catalytic coating layer comprising the copper-containing molecular sieve catalyst described above.

[0010] The present disclosure may further provide an exhaust gas treatment system including the catalytic article, and a method for treating an exhaust stream containing NOx, comprising passing the exhaust stream through the catalytic article or treatment system.

[0011] The present catalysts, catalytic articles, systems, and methods are suitable for treating exhaust gases generated by diesel or gasoline engines, particularly those operating under "lean" combustion conditions where more air is present than is required for stoichiometric combustion.

[0012] The present invention includes, but is not limited to, the following embodiments.

[0013] Embodiment 1: A selective catalytic reduction article comprising a substrate having a catalytic coating on at least a portion of a surface thereof, the catalytic coating being Cu. +2 and Cu(OH) as cations +1 The present invention relates to a copper-containing molecular sieve that contains ion-exchanged copper as a cation, the copper-containing molecular sieve being +2 Perturbed TOT asymmetric stretching vibration peaks corresponding to the cation, and Cu(OH) +1 The perturbed TOT asymmetric stretching vibration peak corresponding to the cation, measured using diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, Cu +2 The integrated peak areas of the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations, and Cu(OH)+1 A selective catalytic reduction article, in which the integrated peak areas of the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations have a ratio of 1 or more.

[0014] Embodiment 2: The copper-containing molecular sieve is characterized in that in the infrared spectrum, +2 Cation and Cu(OH) +1 The perturbed TOT asymmetric stretching vibration peaks corresponding to the cations are located at approximately 900 cm -1 and about 950 cm -1 or copper-containing molecular sieves show Cu in the infrared spectrum. +2 Cation and Cu(OH) +1 The perturbed TOT asymmetric stretching vibration peaks corresponding to the cations are located at approximately 900 cm -1 and about 970 cm -1 3. The selective catalytic reduction article of any preceding embodiment.

[0015] Embodiment 3: Cu +2 The percentage of the total integrated peak area attributable to the perturbed TOT asymmetric stretching vibration peaks corresponding to the cation is Cu +2 The integrated peak areas for the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations were calculated as Cu +2 Cation and Cu(OH) +1 is calculated by dividing the integrated peak area for the perturbed TOT asymmetric stretching vibration peak corresponding to the cation, Cu +2 The selective catalytic reduction article of any preceding embodiment, wherein the percentage of the total integrated peak area attributable to the perturbed TOT asymmetric stretching vibration peak for the cation is 50% or greater.

[0016] Example 4: For copper-containing molecular sieves in the aged state, Cu +2 The perturbed TOT asymmetric stretching vibration peak corresponding to the cation, Cu +2 Cation and Cu(OH) +1The selective catalytic reduction article of any of the preceding embodiments, wherein the contribution to the combined integrated peak area for the cationic perturbed TOT asymmetric stretching vibration peak is increased by 20% or less relative to the contribution for the copper-containing molecular sieve in a fresh state, and the aged state is defined by aging the selective catalytic reduction article at a temperature of about 800° C. for about 16 hours in the presence of air having an HO content of about 10 mol%.

[0017] Embodiment 5: The selective catalytic reduction article of any preceding embodiment, wherein the total amount of copper in the copper-containing molecular sieve, calculated as copper oxide, is about 1.0 wt.% to about 10 wt.%, based on the total mass of the copper-containing molecular sieve.

[0018] Embodiment 6: The selective catalytic reduction article of any preceding embodiment, wherein the copper-containing molecular sieve comprises crystals or agglomerates having an average size of 2.0 microns or less.

[0019] Embodiment 7: The selective catalytic reduction article of any preceding embodiment, wherein the copper-containing molecular sieve comprises a small pore molecular sieve selected from the group consisting of framework types AEI, AFT, AFV, AFX, AVL, CHA, DDR, EAB, EEI, ERI, IFY, IRN, KFI, LEV, LTA, LTN, MER, MWF, NPT, PAU, RHO, RTE, RTH, SAS, SAT, SAV, SFW, TSC, UFI, mixtures thereof, and intergrowths thereof.

[0020] Embodiment 8: The selective catalytic reduction article of any preceding embodiment, wherein the molecular sieve comprises a medium pore molecular sieve selected from the group consisting of framework types AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, SVR, SZR, TER, TON, TUN, UOS, VSV, WEI, WEN, mixtures thereof, and intergrowths thereof.

[0021] Embodiment 9: The selective catalytic reduction article of any preceding embodiment, wherein the molecular sieve comprises a large pore molecular sieve selected from the group consisting of framework types AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, MEI, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY, VET, mixtures thereof, and intergrowths thereof.

[0022] Embodiment 10: The selective catalytic reduction article of any preceding embodiment, wherein the molecular sieve is selected from the group consisting of aluminosilicate zeolites, borosilicates, gallosilicates, SAPO, AlPO, MeAPSO, MeAPO, and combinations thereof.

[0023] Embodiment 11: The selective catalytic reduction article of any preceding embodiment, wherein the molecular sieve has CHA cage and double 6-membered ring building units and is selected from the group consisting of Cu-CHA, Cu-SAPO-34, AEI, Cu-SAPO-18, and combinations thereof.

[0024] Embodiment 12: The selective catalytic reduction article of any preceding embodiment, wherein the selective catalytic reduction article further comprises one or more catalytically active metals selected from the group consisting of manganese, iron, cobalt, nickel, cerium, platinum, palladium, and rhodium, or contains one or more base metals selected from the group consisting of sodium, potassium, magnesium, calcium, strontium, barium, and combinations thereof.

[0025] Embodiment 13: The selective catalytic reduction article of any preceding embodiment, wherein the catalytic coating comprises a first catalytic coating comprising a copper-containing molecular sieve, and a second catalytic coating different from the first catalytic coating.

[0026]

[0041] Embodiment 14: The selective catalytic reduction article of any preceding embodiment, wherein the second catalytic coating comprises a copper-containing molecular sieve that is different from the copper-containing molecular sieve of the first coating.

[0027] Embodiment 15: The selective catalytic reduction article of any preceding embodiment, wherein the second catalytic coating comprises a platinum group metal on a refractory metal oxide support.

[0028] Embodiment 16: The platinum group metal is about 0.5 g / ft of the total volume of the substrate. 3 ~about 30g / ft 3 The selective catalytic reduction article of any preceding embodiment,

[0029]

[0046] Embodiment 17: A catalytic coating comprising a copper-containing molecular sieve is applied to a substrate in an amount of about 0.1 g / in based on the total volume of the substrate. 3 ~ approx. 4.5g / in 3 The selective catalytic reduction article of any preceding embodiment,

[0030] Embodiment 18: The selective catalytic reduction article of any preceding embodiment, wherein the first catalytic coating and the second catalytic coating are in a layered or zonal configuration.

[0031] Embodiment 19: The selective catalytic reduction article of any preceding embodiment, wherein the substrate is a porous wall-flow filter, or a flow-through monolith.

[0032] Embodiment 20: A selective catalytic reduction article according to any preceding embodiment; and a reductant injector in fluid communication with and upstream of the selective catalytic reduction article; An exhaust gas treatment system comprising:

[0033] Embodiment 21: The exhaust gas treatment system of any preceding embodiment, further comprising one or more of a diesel oxidation catalyst, a soot filter, a lean NOx trap (LNT), and an ammonia oxidation catalyst.

[0034] Embodiment 22: A method for treating an exhaust stream containing NOx, comprising passing the exhaust stream through a selective catalytic reduction article or exhaust gas treatment system of any preceding embodiment.

[0035] Embodiment 23: A method for identifying a catalytic material that is stable to aging, comprising: +2 As a cation, and Cu(OH) +1 Providing a plurality of samples each including particles of a copper-containing molecular sieve containing ion-exchanged copper as a cation; +2 Perturbed TOT asymmetric stretching vibration peaks corresponding to cations and Cu(OH) of copper-containing molecular sieves +1 The copper-containing molecular sieve particles are subjected to diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy to evaluate the perturbed TOT asymmetric stretching vibration peak corresponding to the cation; +2 The integrated peak area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation and Cu(OH)+1 and selecting one or more of the samples that exhibit a ratio of 1 or more to the integrated peak area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation.

[0036] Embodiment 24: Cu +2 The percentage of the total integrated peak area attributable to the perturbed TOT bond vibration peaks corresponding to the cation is Cu +2 The integrated peak areas for the perturbed TOT bond vibration peaks corresponding to the cations were calculated as Cu +2 Perturbed TOT bond vibration peaks corresponding to the cation and Cu(OH) +1 is calculated by dividing the integrated peak area for the perturbed TOT bond vibration peak corresponding to the cation, Cu +2 The method of any preceding embodiment, comprising selecting one or more samples having a percentage of the total integrated peak area attributable to perturbed TOT bond vibration peaks for the cations equal to or greater than 50%.

[0037] Embodiment 25. The method of any preceding embodiment, wherein a plurality of copper-containing molecular sieve samples are subjected to DRIFT spectroscopy in a fresh state, aging the plurality of samples in the presence of air having an HO content of about 10 mol % at a temperature of about 800° C. for about 16 hours to form aged samples; subjecting the aged sample to DRIFT spectroscopy; Cu for one or more samples in the aged state +2 The contribution to the total integrated peak area from the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is calculated for one or more samples in the fresh state. +2 selecting one or more of the samples that have an increase of 20% or less in the contribution to the total integrated peak area from the perturbed TOT asymmetric stretching vibration peak corresponding to the cation; The method further comprises:

[0038]

[0041] Embodiment 26: A method of producing a catalyst article, comprising the steps of: developing a process for producing a first composition comprising a copper-containing molecular sieve; and analyzing a sample of the first composition using at least DRIFT spectroscopy to determine whether Cu +2 and Cu(OH) +1 Based on a comparison of the intensities of the perturbed TOT asymmetric stretching vibration peaks corresponding to Cu in the first composition, +2 and Cu(OH) +1 determining the relative amount of Cu +2 and applying the commercially produced first composition made by the process to a substrate to produce a catalyst article.

[0039] These and other features, aspects, and advantages of the present disclosure will become apparent from reading the following detailed description in conjunction with the accompanying drawings, which are briefly described below. The present invention includes any combination of two, three, four, or more of the above-described embodiments, and any combination of two, three, four, or more features or elements described in the present disclosure, whether or not such features or elements are explicitly combined in the description of a particular embodiment herein. The present disclosure, in any of its various aspects and embodiments, is intended to be read as a whole such that any separable features or elements of the disclosed invention are deemed combinable unless the context clearly dictates otherwise. Other aspects and advantages of the present invention will become apparent from the following.

[0040] The disclosure described herein is illustrated by way of example and not by way of limitation in the accompanying drawings. For simplicity and clarity of illustration, features illustrated in the drawings have not necessarily been drawn to scale. For example, the dimensions of some features may be exaggerated relative to other features for clarity. Further, where considered appropriate, reference numerals indicating corresponding or similar elements have been repeated among the drawings. [Brief description of the drawings]

[0041] [Figure 1] 1 is a perspective view of a honeycomb-type substrate support that may include a catalytic article in the form of a washcoat composition according to the present disclosure. [Diagram 2] 2 is an enlarged partial cross-sectional view of FIG. 1 taken along a plane parallel to the end face of the substrate support of FIG. 1 and showing an enlarged view of multiple gas flow paths shown in FIG. 1 in one embodiment in which the substrate support is a monolithic flow-through substrate. [Diagram 3] 2 is a cutaway view of an enlarged portion of FIG. 1, in which the honeycomb-shaped substrate support represents a wall-flow filter substrate monolith. [Figure 4a] 1A-1D are cross-sectional views illustrating coating layers and / or coating zones on one or more substrates according to exemplary embodiments of the present disclosure. [Figure 4b] 1A-1D are cross-sectional views illustrating coating layers and / or coating zones on one or more substrates according to exemplary embodiments of the present disclosure. [Diagram 5] 4 is a graph showing NOx conversion for catalyst coated samples described in Example 1 and Example 2. [Figure 6] 4 is a graph showing NOx conversion for catalyst coated samples described in Example 1 and Example 3. [Figure 7] 1 shows the DRIFT spectra of fresh catalyst coated samples described in Examples 1-3. [Figure 8]1 shows the DRIFT spectra of fresh and aged catalyst coating samples as described in Example 1. [Figure 9] 1 shows the DRIFT spectra of fresh and aged catalyst coating samples as described in Example 3. [Figure 10] 4 is a graph showing NOx conversion for catalyst coated samples described in Example 3 and Example 6. [Figure 11] 1 shows the DRIFT spectra of fresh and aged catalyst coating samples as described in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] The catalyst composition is suitable for treating exhaust gas streams from internal combustion engines, such as gasoline, light duty diesel, and heavy duty diesel engines. The catalyst composition is also suitable for treating emissions from stationary industrial processes, or for catalysis in chemical reaction processes.

[0043] High surface area refractory metal oxide supports are materials used as catalyst supports that receive precious metals, stabilizers, promoters, binders, etc. through association, dispersion, impregnation, or other suitable methods. High surface area refractory metal oxide supports may include activating compounds selected from the group consisting of alumina, zirconia, silica, titania, ceria, lanthana, baria, and combinations thereof.

[0044] Molecular Sieves Molecular sieves generally refer to materials that have an extensive three-dimensional network of oxygen ions containing tetrahedral sites and have a relatively uniform pore size distribution. Zeolites are specific examples of molecular sieves and further include silicon and aluminum. References to "non-zeolitic supports" or "non-zeolitic supports" in the catalyst layer refer to materials that are not zeolites. Examples of such non-zeolitic supports include, but are not limited to, high surface area refractory metal oxides.

[0045] Molecular sieves include small pore, medium pore, and large pore molecular sieves, or combinations thereof. Small pore molecular sieves contain channels defined by up to 8 tetrahedral atoms. Medium pore molecular sieves contain channels defined by 10-membered rings. Large pore molecular sieves contain channels defined by rings of at least 12 tetrahedral atoms.

[0046] Small pore molecular sieves have 8-ring openings, but may have, for example, double 6-ring (D6R) or 6-ring structural units. Cage building units include CHA cages, various modifications of CHA cages, LTA cages, GME cages, and the like.

[0047] The small pore molecular sieve is selected from the group consisting of aluminosilicate molecular sieves, metal-containing aluminosilicate molecular sieves, aluminophosphate (ALPO) molecular sieves, metal-containing aluminophosphate (MeALPO) molecular sieves, silico-aluminophosphate (SAPO) molecular sieves, and metal-containing silico-aluminophosphate (MeSAPO) molecular sieves, and mixtures thereof. For example, the small pore molecular sieve is selected from the group consisting of framework types AEI, AFT, AFV, AFX, AVL, CHA, DDR, EAB, EEI, ERI, IFY, IRN, KFI, LEV, LTA, LTN, MER, MWF, NPT, PAU, RHO, RTE, RTH, SAS, SAT, SAV, SFW, TSC, UFI, and mixtures or intergrowths thereof. For example, the small pore molecular sieve is selected from the group of framework types CHA, LEV, AEI, AFT, AFX, ERI, LTA, SFW, KFI, and DDR.

[0048] The medium pore molecular sieve is selected from the group consisting of framework types AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, SVR, SZR, TER, TON, TUN, UOS, VSV, WEI, WEN, and mixtures or intergrowths thereof. For example, the medium pore molecular sieve is selected from the group consisting of framework types FER, MEL, MFI, and STT.

[0049] The large pore molecular sieve is selected from the group consisting of framework types AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, MEI, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY, VET, and mixtures or intergrowths thereof. For example, the large pore molecular sieve is selected from the group consisting of framework types AFI, BEA, FAU, MAZ, MOR, and OFF.

[0050] For example, the molecular sieve comprises a framework type selected from the group consisting of AEI, BEA (beta zeolite), CHA (chabazite), FAU (zeolite Y), FER (ferrierite), MFI (ZSM-5), and MOR (mordenite). Non-limiting examples of zeolites having these structures include chabazite, faujasite, zeolite Y, ultrastable zeolite Y, beta zeolite, mordenite, silicalite, zeolite X, and ZSM-5.

[0051] Useful molecular sieves have an 8-ring pore opening and double 6-ring secondary building units, for example, those having the structure types AEI, AFT, AFX, CHA, EAB, ERI, KFI, LEV, SAS, SAT, or SAV. Included are any of the isotopic framework materials, such as SAPO, ALPO, and MeAPO materials having the same structure types.

[0052] Aluminosilicate zeolite structures do not contain phosphorus or other metals isomorphously substituted within the framework, i.e., "aluminosilicate zeolites" excludes aluminophosphate materials such as SAPO, ALPO, and MeAPO materials, while the broader term "zeolite" includes aluminosilicates and aluminophosphates.

[0053] In one or more embodiments, the 8-ring small pore molecular sieve has a CHA crystal structure. Copper-containing chabazite is abbreviated as CuCHA. In further embodiments, the molecular sieve may have a SAPO crystal structure, i.e., CuSAPO.

[0054] Synthetic 8-ring small pore molecular sieves (e.g., having a CHA structure) can be produced by mixing a silica source, an alumina source, and a structure directing agent under alkaline aqueous conditions. Typical silica sources include various types of fumed silica, precipitated silica, and colloidal silica, as well as silicon alkoxides. Typical alumina sources include boehmite, pseudoboehmite, aluminum hydroxide, aluminum salts such as aluminum sulfite or sodium aluminate, and aluminum alkoxides. Typically, sodium hydroxide is added to the reaction mixture. A typical structure directing agent for this synthesis is adamantyltrimethylammonium hydroxide, although other amines and / or quaternary ammonium salts can be substituted or added. The reaction mixture is heated with stirring in a pressure vessel to obtain a crystalline product. Typical reaction temperatures range from about 100°C to about 200°C, such as from about 135°C to about 170°C. Typical reaction times range from 1 hour to 30 days, and in some embodiments, from 10 hours to 3 days. At the end of the reaction, the pH is optionally adjusted to 6-10, for example 7-7.5, and the product is filtered and washed with water. An optional acid, for example nitric acid, can be used for pH adjustment. Optionally, the product may be centrifuged. Organic additives can be used to aid in handling and isolation of the solid product. Spray drying is an optional step in the processing of the product. The solid product is heat treated in air or nitrogen. Alternatively, each gas treatment can be applied in various orders, or a mixture of gases can be applied. Typical calcination temperatures are from about 400°C to about 850°C.

[0055] Molecular sieves having the CHA structure can be prepared, for example, according to the methods disclosed in US Pat. Nos. 4,544,538 and 6,709,644, the disclosures of which are incorporated herein by reference.

[0056] The molecular sieve can have a silica-to-alumina ratio (SAR) of from about 1 to about 1000. In some embodiments, the molecular sieve can have a SAR of from about 2 to about 750, from about 5 to about 250, or from about 5 to about 50.

[0057] Advantageously, the molecular sieve of the present catalytic composition is a small pore, medium pore, or large pore molecular sieve.

[0058] Catalytic Molecular Sieves The catalyst contains, for example, ion-exchanged copper, but the Cu in the new sample +2 The atomic percentage (atomic % or at%) of ion-exchanged copper in the Cu state was calculated for a sample aged at 800 °C for 16 h in the presence of 10% H2O / air. +2 The atomic percentages of Cu in the fresh vs. aged samples remain stable compared to that of ion-exchanged copper in the fresh state. As described further herein, such stability has been found to be highly desirable in identifying catalytic materials with improved NOx conversion activity. Preferably, the atomic percentages of the fresh vs. aged samples are within 20%, 15%, 10%, or 5% of each other. Cu +2 The atomic percentage of ion-exchanged copper in the state is based on the total ion-exchanged copper.

[0059] In the present invention, the copper present at the ion exchange sites of the molecular sieve (ion-exchanged copper) is 50 at% (atomic percent) Cu +2 That's it. Other ion-exchanged copper is, for example, Cu(OH) +1 This is after exposure to air and / or moisture and therefore oxidation. Cu +2 The atomic percentages are determined based on analysis of the infrared spectra of fresh and aged samples, which allows for the identification of the relative copper species present in the copper-exchanged catalyst material.

[0060] In some embodiments, the ion-exchanged copper can be identified, for example, by DRIFT spectroscopy (diffuse reflectance infrared Fourier transform spectroscopy), performed using known methods. The copper species can be detected by monitoring the perturbed TOT bond (Si-O-Al and Si-O-Si) vibrations of the molecular sieve. The structural vibrations of the TOT bonds of the molecular sieve are at about 1350 cm for the asymmetric and symmetric vibration modes, respectively. -1 ~Approx. 920cm -1 , and about 850 cm -1 ~Approx. 620cm -1 The perturbed TOT bond vibration is observed due to the strong interaction between the copper ions and the framework oxygens when the copper ions are exchanged into the cationic sites of the molecular sieve. The peak position depends on the nature of the copper ions and the structure of the molecular sieve framework. The peak intensity and peak integrated area may depend on the amount of copper ions in the exchange sites. Therefore, DRIFT spectroscopy is effective for qualitative analysis of the properties of copper-exchanged molecular sieve catalyst materials. In general, the present invention contemplates the use of any vibrational mode that is perturbed (i.e., shifted) by the presence of various metal ion species interacting with the TOT framework of the molecular sieve for characterization. For example, as disclosed herein, copper species can be detected by monitoring the perturbed TOT asymmetric stretching vibrational mode by using DRIFT spectroscopy.

[0061] DRIFT spectroscopy can be performed as in this example. See also Luo et al., "Identification of two types of Cu sites in Cu / SSZ-13 and their unique responses to hydrothermal aging and sulfur poisoning," Catalysis Today, 267 (2016), 3-9, and Kwak et al., "two different cationic positions in Cu-SSZ-13?", Chem. Commun., 2012, 48, 4758-4760.

[0062] In the DRIFT spectrum of the aluminosilicate chabazite CuCHA, the peaks at approximately 1040 and 810 cm -1 In addition to the asymmetric and symmetric vibrations of the unperturbed TOT(Si-O-Al) bond at about 900 cm -1 and about 950 cm -1 , respectively, Al pairs and associated Cu +2 Perturbation of TOT asymmetric stretching vibration by Al and Cu(OH) associated with single Al +1 Two absorptions are observed, which are due to the perturbed TOT asymmetric stretching vibration caused by Cu. +2 Peak and Cu(OH) +1 "peak" refers to perturbed absorptions identified in the DRIFT spectrum. For example, for copper chabazite catalyst material, there is a peak at approximately 900 cm corresponding to the perturbed TOT asymmetric stretching vibration. -1 and about 950 cm -1 The infrared absorption at Cu +2 and Cu(OH) +1 Similarly, for the copper SAPO catalyst material, the presence of a perturbed asymmetric stretching vibration at approximately 900 cm -1 and about 970 cm -1 The infrared absorption at Cu +2 and Cu(OH) +1 can be associated with the presence of

[0063] Without being bound by theory, it is believed that Cu balances the charge of the Al pair. +2 is Cu(OH) associated with single Al. +1 It is believed that the Cu cations are more hydrothermally stable, thereby enabling high NOx reduction activity and high hydrothermal stability of the catalyst. Again, without being bound by theory, it is believed that the Cu cations balance the charge created by the substitution of Si for P in the SAPO molecular sieve. The perturbed TOT bond vibrations for SAPO are related to the structural vibrations of the Si, Al, and P in the tetrahedral "T" sites. Thus, the Cu cations in the molecular sieve framework +2Catalysts with a high relative percentage of (determined by DRIFT analysis as discussed above through identification of perturbed TOT bonds, such as those corresponding to perturbed TOT asymmetric stretching vibrations) can be identified and can provide improved catalytic performance and aging stability.

[0064] In some embodiments, the preferred stability is +2 The integrated peak area of ​​the perturbed TOT asymmetric stretching peak corresponding to the cation (e.g., approximately 900 cm in the DRIFT spectrum) -1 (peak for perturbed TOT bonds in ) and Cu(OH) +1 The integrated peak area of ​​the perturbed TOT asymmetric stretching peak corresponding to the cation (e.g., approximately 950 cm in the DRIFT spectrum) -1 For CuCHA in, or around 970 cm in the DRIFT spectrum -1 For example, the ratio between the peak for the perturbed TOT bond for CuSAPO at +2 The integrated peak areas for the perturbed TOT asymmetric stretching peaks corresponding to Cu(OH) +1 may be 1 or more, 1.2 or more, or 1.5 or more. For example, the ratio of the integrated peak areas may be about 1 to about 5, about 1.2 to about 4, or about 1.5 to about 3.

[0065] In a further embodiment, a suitable copper-exchanged molecular sieve is Cu +2 The contribution of the perturbed TOT asymmetric stretching vibration peak to the total peak area of ​​the perturbed TOT asymmetric stretching vibration peak can be identified in terms of the contribution of the perturbed TOT asymmetric stretching vibration peak to the total peak area of ​​the perturbed TOT asymmetric stretching vibration peak. This can be calculated using the formula given below, where "area Cu +2 " is Cu +2 The integrated peak area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to (i.e., approximately 900 cm in the DRIFT spectrum) -1 (peak at Cu(OH) +1 " is Cu(OH) +1The integrated peak area for the perturbed TOT asymmetric stretching vibration peak corresponding to (i.e., approximately 950 cm in the DRIFT spectrum) -1 and about 970 cm in the DRIFT spectrum for CuCHA. -1 (peak for CuSAPO at 1000 nm).

[0066]

number

[0067] Preferably, Cu +2 The percentage of the total peak area attributable to the perturbed TOT asymmetric stretching vibration peak for is at least 50%, at least 55%, or at least 60%, for example, about 55% to about 95%, about 60% to about 90%, or about 65% to about 85%.

[0068] While the integrated area under each curve for the present perturbation absorption does not correlate to the relative atomic % amounts of the individual copper species present, the maintenance of the ratio with aging indicates an apparently stable structure, which correlates to a material with stable catalytic activity.

[0069] In some embodiments, the aforementioned ratios and percentages may not change substantially between the fresh and aged states for the copper-exchanged molecular sieve. For example, after aging the copper-exchanged molecular sieve in the presence of air with a HO content of about 10 mol % at a temperature of about 800° C. for 16 hours, the Cu +2 The percentage of the total peak area corresponding to the perturbed TOT asymmetric stretching vibration attributable to the perturbed TOT asymmetric stretching vibration peak for may increase by 30% or less, 20% or less, or 10% or less.

[0070] Without wishing to be bound by theory, it is believed that all molecular sieves constructed from CHA and double 6-membered rings will exhibit similar vibrational modes and that Cu cations will perturb the vibrational spectra in a similar manner. Such molecular sieves are CHA, SAPO-34, AEI, and SAPO-18. Other small, medium, and large molecular sieves will exhibit unique vibrational spectra, but Cu cations will perturb the vibrational modes in a similar manner.

[0071] Copper-containing molecular sieves are, for example, Na + Molecular sieve containing (Na + It is prepared, for example, by ion exchange from Na + The calcined form generally refers to the calcined form without ion exchange. In this form, the molecular sieve generally has Na on the exchange sites. + and H + Contains a mixture of cations: Na + The percentage of cation-occupied sites will vary with the particular zeolite batch and recipe. Optionally, the alkali metal molecular sieve is NH4 + It was replaced with NH4 + The mold is used for ion exchange with copper. Optionally, NH4 + Exchange molecular sieve H + It is fired into a mold and can also be used for ion exchange with copper.

[0072] For example, copper can be oxidized with an alkali metal, NH4, using a copper salt such as copper acetate or copper sulfate, as disclosed in U.S. Pat. No. 9,242,238, the disclosure of which is incorporated herein by reference. + , or H + Ion exchange into molecular sieves of the type. For example, Na + , NH4 + , or H + The molecular sieves of type 1 are mixed with the salt water solution and stirred at elevated temperature for a suitable period of time. The slurry is filtered and the filter cake is washed and dried.

[0073] Additionally, as disclosed in U.S. Pat. No. 9,272,272, the disclosure of which is incorporated herein by reference, at least a portion of the catalytically active metal may be included during the molecular sieve synthesis process such that the prepared colloid contains a structure directing agent, a silica source, an alumina source, and a metal ion (e.g., copper) source.

[0074] The total amount of copper in the molecular sieve is, for example, about 1.0 wt% to about 10 wt% based on the total weight of the copper-containing molecular sieve. In some embodiments, the total amount of copper in the molecular sieve may be about 1.5 wt% to about 9 wt%, about 2.0 wt% to about 8 wt%, or about 3.0 wt% to about 7 wt% based on the total weight of the copper-containing molecular sieve.

[0075] The total amount of copper includes ion-exchanged copper and copper associated with the molecular sieve but not ion-exchanged.

[0076] The amount of copper in the molecular sieve is reported as the oxide, CuO. The total dry mass of the molecular sieve includes any added / exchanged metals such as copper.

[0077] The total amount of copper in a molecular sieve, such as an aluminosilicate zeolite, can also be defined by the atomic ratio of copper to aluminum. For example, the Cu / Al atomic ratio can be about 0.20 to about 0.50. In some embodiments, the Cu / Al atomic ratio can be about 0.25 to about 0.50, about 0.3 to about 0.50, or about 0.35 to about 0.50.

[0078] Each of the copper-containing molecular sieves may have a sodium content (reported as Na2O on a volatile matter free basis) of less than 2 wt. % based on the total weight of the catalyst composition. In a more specific embodiment, the sodium content is less than 2500 ppm. Each of the molecular sieves may have a sodium to aluminum atomic ratio of less than about 0.7, e.g., from about 0.02 to about 0.7. Each of the molecular sieves may have a copper to sodium atomic ratio of greater than about 0.5, e.g., from about 0.5 to about 50.

[0079] The copper-containing molecular sieve has a molecular weight of at least about 400 m, as determined in accordance with DIN 66131. 2 / g, at least about 550m 2 / g, or at least about 650m 2 / g, for example, about 400 to about 750 m 2 / g, or about 500 to about 750 m 2 The molecular sieve may exhibit a BET surface area of ​​about 10 nanometers to about 20 microns, preferably about 0.1 microns to about 2.0 microns, as determined by scanning electron microscopy (SEM). Advantageously, the average crystal size is 0.5 microns or less, or 2.0 microns or less.

[0080] Catalyst Coating / Substrate The molecular sieve may be provided in the form of a powder or spray-dried material that is mixed with or coated with a suitable modifier. Modifiers include silica, alumina, titania, zirconia, and refractory metal oxide binders (e.g., zirconium precursors). The powder or spray material, after mixing or coating with a suitable modifier, may optionally be formed into a slurry, for example with water, which is deposited on a suitable substrate as part of a catalyst coating, for example, as disclosed in U.S. Pat. No. 8,404,203, the disclosure of which is incorporated herein by reference.

[0081] The catalytic coating contains one or more supports containing active catalytic species. The catalytic coating may typically be applied in the form of a washcoat, containing a support having catalytically active species thereon. The washcoat is formed by making a slurry containing a particular solids content (e.g., 10-60% by weight) of the support in a liquid vehicle, which is then coated onto the substrate, dried, and calcined to provide a coating layer. When multiple coating layers are applied, the substrate is dried and / or calcined after each layer is applied. A final calcination step is performed after the desired number of multiple layers have been applied.

[0082] The coating layer of the molecular sieve can be produced using a binder, for example, a ZrO2 binder derived from a suitable precursor, such as zirconyl acetate, or any other suitable zirconium precursor, such as zirconyl nitrate. The zirconyl acetate binder provides a catalyst coating that remains homogeneous and intact after heat aging, for example when the catalyst is exposed to high temperatures of at least about 600°C, for example about 800°C or higher, and high water vapor environments of about 5% or about 10% or more. Other binders that may be suitable include, but are not limited to, alumina and silica. Alumina binders include aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide. Aluminum salts and colloidal forms of alumina can also be used. Silica binders include various forms of SiO2, including colloidal silica. The binder composition can include any combination of zirconia, alumina, and silica.

[0083] Any of the present coating layers may contain ZrO2 and / or Al2O3 binders.

[0084] The term "catalyst" or "catalyst composition" refers to a material that promotes a chemical reaction. A catalyst includes a "catalytically active species" and a "support" that supports or supports the active species. For example, molecular sieves, including zeolites, are carriers / supports for the present copper-active catalytic species. Similarly, refractory metal oxide particles can be supports for platinum group metal catalytic species.

[0085] The copper-containing catalysts are highly effective as selective catalytic reduction (SCR) catalysts for nitrogen oxides (NOx) to N2. Typically, a reducing agent such as ammonia is used. Urea can be used as the ammonia precursor.

[0086] Catalytically active species are also referred to as "promoters" because they promote a chemical reaction. For example, the present copper-containing molecular sieves may be referred to as copper-promoted molecular sieves. "Promoted molecular sieves" refers to molecular sieves to which catalytically active species have been purposefully added.

[0087] The term "substrate" generally refers to a monolithic material, such as a flow-through monolith or a monolithic wall-flow filter, on which a catalytic coating is disposed. In one or more embodiments, the substrate is ceramic or metal having a honeycomb structure. Any suitable substrate may be used, such as a monolithic substrate of the type having fine, parallel gas flow passages extending from the inlet end to the outlet end of the substrate, the passages being open to the fluid flow. The passages are substantially linear paths from their fluid inlets to their fluid outlets, and are defined by walls on which the catalytic coating is disposed such that gas flowing through the passages contacts the catalytic material. The flow passages of the monolithic substrate are thin-walled channels and may be of any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, and the like. Such structures may contain from about 60 to about 900, or more, gas inlet openings (i.e., cells) per square inch of cross section.

[0088] The substrate is three-dimensional, similar to a cylinder, having a length, a diameter, and a volume. The shape does not necessarily conform to a cylinder. The length is the axial length defined by the inlet and outlet ends.

[0089] The flow-through monolith substrate may be, for example, about 50 in 3 ~About 1200in 3 , a cell density of about 200 to about 400 cpsi, and a wall thickness of about 50 to about 150 microns, or about 200 microns.

[0090] The substrate may be a "flow-through" monolith as described above. Alternatively, the catalyst coating may be placed on a wall-flow diesel particulate filter (DPF), thereby producing a catalyzed soot filter (CSF), or a catalyzed DPF (CDPF). When a wall-flow substrate is utilized, the resulting system is capable of removing particulate matter along with gaseous pollutants. Wall-flow filter substrates may be fabricated from materials commonly known in the art, such as cordierite, aluminum titanate, or silicon carbide. The loading of the catalyst coating on a wall-flow substrate depends on substrate properties such as porosity and wall thickness, and is typically lower than the loading of the catalyst on a flow-through substrate.

[0091] Wall-flow filter substrates useful for supporting SCR catalyst coatings have a plurality of fine, substantially parallel gas flow passages extending along the longitudinal axis of the substrate. Typically, each passage is plugged at one end of the substrate body, with alternating passages plugged at the opposite end face. Such monolithic supports may contain up to about 700 or more passages (or "cells") per square inch of cross section, although much fewer may be used. For example, a typical support will usually have about 100 to about 300 cells per square inch ("cpsi"). The cells may have a rectangular, square, circular, oval, triangular, hexagonal, or other polygonal shaped cross section. Wall-flow substrates typically have a wall thickness of about 150 microns to about 500 microns, e.g., about 200 microns to about 350 microns. Wall-flow filters generally have a wall porosity of at least 40% and an average pore size of at least 10 microns prior to the deposition of the catalyst coating. For example, the wall-flow filter has a wall porosity of about 50 to about 75%, and an average pore size of about 10 to about 30 microns, prior to disposing the catalytic coating.

[0092] 1 and 2 show an exemplary substrate 2 in the form of a flow-through substrate coated with a washcoat composition described herein. With reference to FIG. 1, the exemplary substrate 2 has a cylindrical shape, a cylindrical outer surface 4, an upstream end surface 6, and a corresponding downstream end surface 8 identical to end surface 6. The substrate 2 has a plurality of fine, parallel gas flow passages 10 formed therein. As can be seen in FIG. 2, the flow passages 10 are formed by walls 12 and extend through the carrier 2 from the upstream end surface 6 to the downstream end surface 8, the passages 10 are unobstructed, and a fluid, e.g., a gas stream, can flow longitudinally through the carrier 2 via the gas flow passages 10 therein. As can be more easily seen in FIG. 2, the walls 12 are sized and configured such that the gas flow passages 10 have a substantially regular polygonal shape. As shown, the washcoat composition can be applied in multiple different layers if desired. In the illustrated embodiment, the washcoat consists of both a separate bottom washcoat layer 14 attached to the wall 12 of the carrier member and a second separate top washcoat layer 16 coated over the bottom washcoat layer 14. The invention can be practiced with one or multiple (e.g., two, three or four) washcoat layers and is not limited to the illustrated two-layer embodiment.

[0093] Alternatively, Figures 1 and 3 may show an exemplary substrate 2 in the form of a wall-flow filter substrate coated with a washcoat composition described herein. As can be seen in Figure 3, the exemplary substrate 2 has a plurality of passages 52. The passages are tubularly surrounded by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. The alternating passages are plugged at the inlet end by inlet plugs 58 and at the outlet end by outlet plugs 60, forming an opposing checkerboard pattern at the inlets 54 and outlets 56. Gas flow 62 enters through the unplugged channel inlets 64, is stopped by the outlet plugs 60, and diffuses through the channel walls 53 (which are porous) to the outlet side 66. The gas cannot return to the inlet side of the wall due to the inlet plugs 58. The porous wall-flow filters used in the present invention are catalyzed in that the walls of the elements have one or more catalytic materials thereon or contained therein. The catalytic material may be present only on the inlet side, only on the outlet side, on both the inlet and outlet sides of the element walls, or the walls themselves may consist, in whole or in part, of catalytic material. The invention includes the use of one or more layers of catalytic material on the inlet and / or outlet walls of the element.

[0094] Catalytic wall-flow filters are disclosed, for example, in U.S. Patent No. 7,229,597, the disclosure of which is incorporated herein by reference. This reference teaches how to apply a catalytic coating so that the coating penetrates the porous wall, i.e., is distributed throughout the wall. Flow-through and wall-flow substrates are also taught, for example, in U.S. Patent Application No. 62 / 072,687, published as WO2016 / 070090.

[0095] The catalytic coating may be on the wall surface and / or within the pores of the wall, i.e., "in" and / or "on" the filter wall. Thus, the phrase "having a catalytic coating thereon" means on any surface, for example, on the wall surface and / or on the pore surfaces.

[0096] The inlet end of the substrate is synonymous with the "upstream" or "front" end. The outlet end is synonymous with the "downstream" or "rear" end. The substrate will have a length and a width.

[0097] The ceramic substrate may be made from any suitable high melting point material, such as, for example, cordierite, cordierite-alpha-alumina, aluminum titanate, silicon carbide, silicon nitride, zircon mullite, spodumene, alumina-silica-magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, alpha-alumina, aluminosilicate, and the like.

[0098] Substrates useful in the present invention may be metallic, including one or more metals or metal alloys. Metal substrates can be used in a variety of forms, such as pellets, corrugated sheets, or monolithic forms. Specific examples of metal substrates include heat-resistant base metal alloys, particularly alloys in which iron is a substantial or major component. Such alloys can contain one or more of nickel, chromium, and aluminum, the sum of which advantageously comprises at least about 15 wt. % (weight percent) of the alloy, e.g., about 10 to about 25 wt. % chromium, about 1 to about 8 wt. % aluminum, and 0 to about 20 wt. % nickel.

[0099] The catalyst coating includes one or more thin, adherent coating layers, at least one of which includes a copper-containing catalyst. The coating is disposed on and adhered to a substrate. The entire coating includes individual "coating layers." The catalyst coating may be "zoned" and may include zoned catalyst layers. This may also be described as "laterally zoned." For example, a first layer may extend from the inlet end toward the outlet end and may extend about 10% to about 90%, about 10% to about 50%, or about 10% to about 25% of the length of the substrate. A second layer may extend from the outlet end toward the inlet end and may extend about 10% to about 90%, about 10% to about 50%, or about 10% to about 25% of the length of the substrate. The first and second layers may be adjacent to each other and not overlap each other. Alternatively, the first and second layers may overlap a portion of each other to provide a third "intermediate" zone. The intermediate zone may, for example, extend from about 5% to about 80% of the length of the substrate. Alternatively, the first layer may extend from the exit end and the second layer may extend from the entrance end.

[0100] The upstream zone is upstream of the downstream zone. A zone of a catalytic substrate is defined as a cross-section having some coating structure thereon.

[0101] The first and second layers may each extend the entire length of the substrate, or each extend a portion of the substrate's length, and may overlap, either partially or entirely, above or below each other. Each of the first and second layers may extend from either the inlet end or the outlet end. Coating layers that overlap, either partially or entirely, above or below each other may be referred to as "top" and "bottom" coating layers, with the top layer being "above" the bottom layer. A top layer above a bottom layer means that they may be in direct contact or may have an intermediate layer between them.

[0102] The first and / or second coating layer may be in direct contact with the substrate. Alternatively, one or more layers of "undercoats" may be present, whereby at least a portion of the first and / or second coating layer is not in direct contact with the substrate (rather it is in contact with the undercoat). One or more layers of "overcoats" may also be present, whereby at least a portion of the first and / or second coating layer is not directly exposed to the gas stream or atmosphere (rather it is in contact with the overcoat).

[0103] The first and second coating layers may be in direct contact with each other, with no "middle" overlapping zone. Alternatively, the first and second coating layers may not be in direct contact, with a "gap" between the two zones. In the case of an "undercoat" or "overcoat", the gap between the first and second SCR layers is referred to as the "middle layer".

[0104] An undercoat is a layer "below" an additional coating layer, an overcoat is a layer "on" an additional coating layer, and an interlayer is a layer "between" two additional coating layers.

[0105] The interlayers, undercoats, and overcoats may contain one or more catalysts, or may be catalyst-free.

[0106] The catalytic coating may include two or more identical layers, for example, two or more identical layers including the copper-containing catalyst.

[0107] Figures 4a and 4b show some possible coating layer configurations having two coating layers. A substrate wall 200 is shown with coating layers 201 (top coat) and 202 (bottom coat) disposed thereon. This is a simplified illustration, and in the case of a porous wall-flow substrate, the pores and coatings attached to the pore walls are not shown, and plugged ends are not shown. In Figure 4a, the bottom coating layer 202 extends about 50% of the length of the substrate from the outlet, and the top coating layer 201 extends more than about 50% of the length of the substrate from the inlet and overlaps a portion of layer 202, providing an upstream zone 203, a middle zone 205, and a downstream zone 204. In Figure 4b, coating layers 201 and 202 each extend the entire length of the substrate, and the top layer 201 overlaps the bottom layer 202. The substrate in Figure 4b does not contain a zoned coating configuration. In Figures 4a and 4b, either or both of layers 201, 202 may contain the present copper-containing molecular sieves. Figures 4a and 4b may be useful for illustrating coating compositions on wall-through or flow-through substrates.

[0108] The catalytic coating, and each zone of the catalytic coating, or any portion of the coating, may, for example, have a coating density of about 0.3 g / in 3 ~ approx. 4.5g / in 3 on the substrate. This refers to the dry solid mass per volume of substrate, e.g., per volume of honeycomb monolith. The amount of base metal, i.e., copper, is only a part of the catalyst coating, including the molecular sieve. The amount of copper per volume may be, for example, about 0.2% to about 10% of the above value. The amount of copper per volume is the copper concentration. The amount of copper-containing molecular sieve per volume is the molecular sieve concentration. The concentration is for a cross-section of the substrate, or for the entire substrate.

[0109] CATALYST ARTICLES AND SYSTEMS The term "catalytic article" refers to an element used to promote a desired reaction. The catalytic article includes a substrate having a catalytic coating disposed thereon.

[0110] The system contains two or more items, for example, a first SCR item and a second SCR item. The system may also include one or more items, including a reductant injector, a diesel oxidation catalyst (DOC), a soot filter, an ammonia oxidation catalyst (AMOx), or a lean NOx trap (LNT).

[0111] An article that contains a reductant injector is a reduction article. The reduction system includes a reductant injector, and / or a pump, and / or a reservoir, and the like.

[0112] The treatment system may further include a diesel oxidation catalyst, and / or a soot filter, and / or an ammonia oxidation catalyst. The diesel particulate filter (DPF) may be uncatalyzed or may be catalyzed, thereby creating a catalyzed soot filter (CSF). For example, the treatment system may include, from upstream to downstream, a DOC, a CSF, an article containing a urea injector, the zoned SCR article, or a first SCR article and a second SCR article, and an article containing AMOx.

[0113] An alternative system may contain a lean NOx trap (LNT) followed by a SCR catalyst coated on a particulate filter (SCRoF) and, optionally, a zoned SCR article containing an AMOX catalyst. In this system, both the SCRoF and the SCR article may contain the present catalyst.

[0114] An undercoat layer comprising the AMOx catalyst may be present in a downstream zone of the substrate, for example, the AMOx undercoat layer may extend from about 10% to about 80% of the length of the substrate of the article from the exit end toward the entrance end.

[0115] The AMOx layer may also be present on a second substrate of a second downstream article to provide a downstream AMOx article.

[0116] AMOx catalysts are taught, for example, in U.S. Patent Application Publication No. 2011 / 0271664, the disclosure of which is incorporated herein by reference. The ammonia oxidation (AMOx) catalyst can be a supported precious metal component effective for removing ammonia from exhaust gas streams. The precious metal can include ruthenium, rhodium, iridium, palladium, platinum, silver, or gold. For example, the precious metal component includes a physical mixture or a chemically or atomically doped combination of the precious metals. The precious metal component includes, for example, platinum. The platinum can be present in an amount of about 0.008% to about 2 wt% relative to the AMOx catalyst.

[0117] The precious metal components are typically deposited on a high surface area refractory metal oxide support. Examples of suitable high surface area refractory metal oxides include alumina, silica, titania, ceria, and zirconia, as well as physical mixtures, chemical combinations, and / or atomically doped combinations thereof. In certain embodiments, the refractory metal oxide may contain mixed oxides such as silica-alumina, amorphous or crystalline aluminosilicates, alumina-zirconia, alumina-lanthana, alumina-manganesia, alumina-baria, alumina-ceria, and the like. Exemplary refractory metal oxides have a surface area of ​​about 50 to about 300 m. 2 The material contains high surface area γ-alumina having a specific surface area of ​​1.0 μm / g.

[0118] The AMOx catalyst may include a zeolitic or non-zeolitic molecular sieve, for example selected from those of the AEI, CHA, FAU, BEA, MFI, and MOR types. The molecular sieve may be physically mixed with an oxide-supported platinum component. In an alternative embodiment, the platinum may be distributed on the exterior surface or within the channels, cavities, or cages of the molecular sieve.

[0119] This embodiment, including a first catalyst article and a second catalyst article, may be referred to as a "multi-component" or "multi-brick" system. A "brick" may refer to a single article, such as a monolith or a filter.

[0120] Advantageously, each of the multi-component articles may contain a substrate that contains the zoned or layered coatings disclosed herein.

[0121] The catalytic article is effective to catalyze the reduction of nitrogen oxides (NOx) in the presence of a reductant, such as ammonia or urea. During operation, the reductant is metered periodically into the exhaust stream from a location upstream of the SCR article. The injector is in fluid communication with the SCR article and is upstream of the SCR article. The injector may also be coupled to a reductant reservoir and a pump.

[0122] The present articles, systems, and methods are suitable for treating exhaust gas streams from mobile sources such as trucks and automobiles. The articles, systems, and methods are also suitable for treating exhaust streams from stationary sources such as power generation equipment.

[0123] Ammonia is the typical reductant for SCR reactions for stationary power plant exhaust treatment, while urea is the typical SCR reductant used for mobile source exhaust treatment. Urea is decomposed into ammonia and carbon dioxide prior to or on contact with the SCR catalyst, and ammonia serves as a NOx reductant.

[0124] The articles, systems, and methods described herein provide high NO xThe term "fresh" is defined as the state of the catalyst article immediately after manufacture, and the term "fresh catalytic activity" is defined as the catalytic performance in the "fresh" condition. The term "aged" is defined as the state of the catalyst article after hydrothermal aging for a specified period of time, and the term "aged catalytic activity" is defined as the catalytic performance in the "aged" condition. The catalytic performance can be defined for a particular test temperature. For example, the present catalyst article has been hydrothermally aged for 80,000 h. -1 At least 50%, preferably at least 75% (e.g., about 50% to about 99%) of aged NO at 200° C., measured at a gas hourly space velocity of 1000 nm. x The catalyst article can demonstrate a conversion rate of 80,000 h in a gas mixture of 500 ppm NO, 500 ppm NH3, 10% O2, 5% H2O, and the balance N2 under steady-state conditions in a laboratory reactor. -1 At least 70%, preferably at least 85% (e.g., about 70% to about 99%) of the aged NO2 at 450° C. is removed, as measured by gas hourly space velocity relative to the volume of the x The conversion rate can be shown. Aged catalysts satisfying the above requirements are subjected to such aging conditions prior to evaluation, where the catalyst is hydrothermally aged in a tube furnace in a gas stream containing 10% H2O, 10% O2, balance N2 at 650°C for 50 hours, 750°C for 5 hours, or 800°C for 16 hours. Such SCR activity measurements are demonstrated in U.S. Patent No. 8,404,203.

[0125] NO x SCR performance such as conversion rate was measured, for example, from 200°C to 600°C with a temperature ramp of 0.5°C / min, and NO x 500 ppm (high-speed SCR conditions: NO2 / NOx = 0.5, or standard SCR conditions: NO2 / NOx = 0), 500 ppm NH3, 10% O2, 5% H2O, and the balance N2, under pseudo-steady-state conditions for 80,000 h. -1 It is measured in terms of gas hourly space velocity relative to the volume of the gas.

[0126] NOx conversion is defined as the combined mol% conversion of NO and NO2. High values ​​are desirable.

[0127] The term "exhaust stream" or "exhaust gas stream" refers to any combination of flowing gases that may contain solid or liquid particulate matter. The stream includes gaseous components, for example, the exhaust of a lean-burn engine, which may contain certain non-gaseous components such as liquid droplets, solid particulates, etc. The exhaust stream of a lean-burn engine typically further includes products of combustion, products of incomplete combustion, oxides of nitrogen, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and / or nitrogen.

[0128] In the present exhaust gas treatment method, an exhaust gas stream passes through the SCR article, SCR system, or exhaust gas treatment system by entering at an upstream end and exiting at a downstream end.

[0129] Certain embodiments relate to the use of articles, systems, and methods for removing NOx from the exhaust gases of internal combustion engines, particularly diesel engines, operating under combustion conditions where more air is present than is required for stoichiometric combustion, i.e., lean conditions.

[0130] The term "vehicle" refers to any vehicle having an internal combustion engine, including, for example, automobiles, sport utility vehicles, minivans, vans, trucks, buses, garbage trucks, freight trucks, construction vehicles, heavy machinery, military vehicles, agricultural vehicles, and the like.

[0131] "Platinum group metal component" refers to a platinum group metal or one of their oxides. "Rare earth metal component" refers to one or more oxides of the lanthanum series as defined in the Periodic Table of the Elements, which includes lanthanum, cerium, praseodymium, and neodymium.

[0132] D90 particle size distribution indicates that 90% of particles (by number) have a Feret's diameter below a certain size, as measured by scanning electron microscope (SEM) or transmission electron microscope (TEM) for submicron-sized particles, and by particle size analyzer for support-containing particles (micron-sized). Average particle size is synonymous with D50, meaning that half of the population is above this point and half is below. Particle size can be measured by laser light scattering techniques, for example, using dispersions or dry powders according to ASTM method D4464. Particle size analyzers measure the number distribution of individual particles as a function of size. Individual particles can be single crystals or aggregates of smaller crystals.

[0133] Identification of age-stable catalytic materials As is apparent from the above and accompanying examples, the present disclosure may be particularly directed to a method for identifying useful catalytic materials. The use of DRIFT spectroscopy in particular allows for the evaluation of a number of copper-containing molecular sieve samples to identify materials that are expected to be useful as catalytic materials, and more particularly, to identify materials that may exhibit aging stability.

[0134] The method for identifying the catalyst material is as follows: +2 As a cation, and Cu(OH) +1 The method can include providing a plurality of samples, each of which includes particles of a copper-containing molecular sieve that contains ion-exchanged copper as a cation. The copper-containing molecular sieve material can have any of the configurations described elsewhere herein.

[0135] The various samples may be in particulate form or may be milled as necessary to provide the necessary morphology for subjecting the particles of the copper-containing molecular sieve to diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. DRIFT spectroscopy is used to determine the amount of Cu in the copper-containing molecular sieve. +2 Perturbed TOT vibration peaks corresponding to cations and Cu(OH) in copper-containing molecular sieves +1A perturbed TOT vibration peak corresponding to the cation can be evaluated. As described elsewhere herein, such information can be used to identify the nature of the copper cation in the copper-containing molecular sieve. Furthermore, such information can be directly related to the NOx conversion activity and aging stability that would be expected in the copper-containing molecular sieve.

[0136] Thus, the method may further include selecting one or more of the samples for which the DRIFT data indicates the utility discussed elsewhere herein. For example, the copper-containing molecular sieve may be selected from the group consisting of Cu +2 The peak integral area of ​​the perturbed TOT vibration peak corresponding to the cation and Cu(OH) +1 Useful samples can be identified that exhibit a ratio of 1 or greater between the peak integrated area of ​​the perturbed TOT vibrational peak corresponding to the cation.

[0137] The additional features described herein as also showing utility may be applied in the alternative or in any combination to identify suitable samples for use in producing a catalyst composition or catalyst article. For example, as already described above, Cu +2 The percentage of the total integrated peak area attributable to the integrated peak area for the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is Cu +2 The integrated peak areas for the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations were calculated as Cu +2 Perturbed TOT bond vibration peaks corresponding to the cation and Cu(OH) +1 The area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation can be calculated by dividing the area of ​​the perturbed TOT asymmetric stretching vibration peak by the total peak integral area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation. +2 The method may include selecting one or more samples for which the percentage of the total integrated peak area attributable to the perturbed TOT bond vibration peak for is 50% or more.

[0138] Optionally, additional processing steps can be performed to confirm the aging stability of useful samples. For example, the samples subjected to DRIFT spectroscopy discussed above may be in a fresh state, among others. As above, the method can further include aging the samples (e.g., at a temperature of about 800° C. for about 16 hours in the presence of air having an HO content of about 10 mol %) to form aged samples. Thereafter, the method can include subjecting the aged samples to DRIFT spectroscopy and determining the Cu content of the copper-containing molecular sieve in the aged state. +2 The percentage of the total integrated peak area attributable to the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations is Cu for the fresh copper-containing molecular sieves. +2 and selecting one or more of the samples that exhibit a 20% or less increase in the percentage of the total integrated peak area attributable to the perturbed TOT asymmetric stretching vibration peak corresponding to the cation.

[0139] The method thus makes it possible to identify useful catalytic materials that can be expected to exhibit good NOx conversion activity and that may also be age-stable. Thus, new catalytic materials can be more easily identified based on spectroscopic analysis without the need for other detailed testing techniques.

[0140] The articles "a" and "an" herein refer to one or more than one (e.g., at least one) of its grammatical object. All ranges cited herein are inclusive. The term "about" used throughout is used to describe and account for small variations. For example, "about" can mean that the numerical value may be modified by ±5%, ±4%, ±3%, ±2%, ±1%, ±0.5%, ±0.4%, ±0.3%, ±0.2%, ±0.1%, or ±0.05%. All numerical values ​​are modified by the term "about", whether or not expressly stated. Numeric values ​​modified by the term "about" include the particular specified value. For example, "about 5.0" includes 5.0.

[0141] All parts and percentages are by weight unless otherwise indicated. Weight percent (wt%) is based on the total composition not including any volatile materials, i.e., based on the dry solids content, unless otherwise indicated.

[0142] All U.S. patent applications, published patent applications, and patents mentioned herein are hereby incorporated by reference.

[0143] [Example 1] SCR catalyst A catalytic coating containing CuCHA zeolite with an SAR of 17, 4.0 wt% CuO, and a Cu / Al ratio of 0.295, and a zirconium oxide binder was placed on a cellular ceramic monolith with a cell density of 400 cpsi and a wall thickness of 6 mils by a washcoat process. The coated monolith was dried at 110°C and calcined at about 550°C for 1 hour. The coating process consisted of a 2.1 g / in zeolite coating of which 5% was zirconium oxide binder. 3 This resulted in a catalyst loading rate of 1.0.

[0144] [Example 2] SCR catalyst A catalytic coating containing CuCHA zeolite with a SAR of 20, 3.8 wt% CuO, and a Cu / Al ratio of 0.325, and a zirconium oxide binder was placed on a cellular ceramic monolith with a cell density of 400 cpsi and a wall thickness of 6 mils by a washcoat process. The coated monolith was dried at 110°C and calcined at about 550°C for 1 hour. The coating process consisted of a 2.1 g / in zeolite coating of which 5% was zirconium oxide binder. 3 This resulted in a catalyst loading rate of 1.0.

[0145] [Example 3] SCR catalyst A catalytic coating containing CuCHA zeolite with an SAR of 25, 3.5 wt% CuO, and a Cu / Al ratio of 0.365, and a zirconium oxide binder was placed on a cellular ceramic monolith with a cell density of 400 cpsi and a wall thickness of 6 mils by a washcoat process. The coated monolith was dried at 110°C and calcined at about 550°C for 1 hour. The coating process consisted of a 2.1 g / in zeolite coating of which 5% was zirconium oxide binder. 3 This resulted in a catalyst loading rate of 1.0.

[0146] [Example 4] NOx conversion test for the catalytic coatings of Examples 1 to 3 NO x The conversion was measured in a laboratory reactor at 200°C to 600°C with a temperature ramp of 0.5°C / min, in a gas mixture of 500 ppm NO, 500 ppm NH3, 10% O2, 5% H2O, balance N2, under pseudo-steady-state conditions for 80,000 h. -1 The NOx conversion is reported as mol % and is measured as NO and NO2.

[0147] The coated monoliths of Examples 1-3 were hydrothermally aged in the presence of 10% HO / air at 800°C for 16 hours. Figure 5 shows the NOx conversion of Example 1 versus Example 2. Figure 6 shows the NOx conversion of Example 1 versus Example 3. Example 1 was superior in terms of NOx conversion under both aging conditions.

[0148] [Example 5] DRIFT spectroscopy of the catalytic coatings of Examples 1 to 3 DRIFT measurements were performed on a THERMO NICOLET FT-IR analyzer with an MCT (HgCdTe) detector and a Harrick environmental chamber with ZnSe windows. Samples were ground into fine powder with a mortar and pestle and placed in a sample cup. The powder was dehydrated at 400 °C for 1 h in flowing Ar at 40 mL / min, cooled to 30 °C, and spectra were recorded using KBr as a reference. Copper species in the zeolite were identified by infrared spectroscopy by monitoring the perturbed TOT bond (Si-O-Al and Si-O-Si) vibrations. The structural vibrations of the TOT bonds in the zeolite were observed at 1350–920 cm for asymmetric and symmetric vibrational modes, respectively. -1 , and 850-620 cm -1 The perturbed TOT bond vibration is observed when copper ions are exchanged into the cationic sites of the zeolite structure due to the strong interaction between the copper ions and the adjacent oxygen atoms in the framework. The peak position depends on the state of the charge compensating cations and the structure of the zeolite framework. The peak intensity depends on the amount of charge compensating cations at the exchange sites.

[0149] The DRIFT spectra of the fresh CuCHA samples of Examples 1, 2, and 3 are shown in FIG. -1 In addition to the asymmetric and symmetric vibrations of the unperturbed TOT (Si-O-Al) bond in -1 It appeared at 900cm -1 The peak at is due to Cu associated with Al pairs. 2+ Due to the perturbed TOT asymmetric stretching vibration at 950 cm -1 The peak at is Cu(OH) associated with single Al. + The peak fitting was performed in Origin 9.1 software. The peaks were modeled as Gaussian peaks and the peak fitting was performed until a chi-square tolerance of 1E-6 was reached. The peaks at 900 and 950 cm for the new sample were -1The peak areas associated with the perturbed vibrational modes are listed in Table 1. 2+ Supporting ions, 900cm -1 The perturbed TOT peak at has the largest area, which is due to the presence of Cu in Example 1. +2 is the predominant copper species, and -1 The peak areas of 900 and 950 cm -1 The total peak area is 71% of the total peak area including the sum of the peak areas in Cu 2+ In addition to a large amount of Cu(OH) +1 Including (950cm -1 (supported by the increase in the area under the TOT peak at 900 and 950 cm -1 ) for the total peak area including 900 cm -1 The percentages of the peak areas of the high NO x It shows high hydrothermal stability and reduction activity, and without being bound by theory, it is believed that Cu balances the charge of the Al pair. 2+ The ion is Cu(OH) which balances the charge of the single Al. +1 It is considered to be more stable.

[0150] As shown in FIG. 8 and Table 2, hydrothermal aging at 800° C. significantly reduced the peaks at 900 and 950 cm for the copper-exchanged molecular sieve of Example 1. -1 This is because the relative TOT peak area in the copper-exchanged molecular sieve of Example 1 was not changed. +2 and Cu(OH) +1 This also confirms that the relative atomic percentage of Cu(OH) did not change with aging, thus demonstrating the high hydrothermal stability of Example 1. For Example 3, after aging at 800° C., +1 The perturbed TOT peak (950 cm -1 ) signal is greatly reduced, and Cu 2+ The perturbed TOT peak (900cm -1 ) increases (Figure 9) and the signal at 900 cm -1The peak percentage increased from 43% to 76% (Table 3). The total peak area decreased from 382 to 320.

[0151] Without wishing to be bound by theory, Cu(OH) +1 The species is Cu +2 It is suggested that the total Cu cation species, [Cu +2 +Cu(OH) +1 ], Cu +2 It is important to note that this only suggests that the relative proportions of

[0152] [Table 1]

[0153] [Table 2]

[0154] [Table 3]

[0155] 900 cm for the copper-exchanged molecular sieve of Example 1 -1 % Peak Area of ​​Peak (A900 cm-1 It can be seen that the 900 cm % increase (3 / 71) by only about 4% upon aging. -1 The % peak area of ​​the peak increased by about 77% (33 / 43). Thus, as discussed in Example 4, the copper-exchanged molecular sieve of Example 1 exhibited desirable aging stability and improved NOx conversion performance.

[0156] [Example 6] SCR catalyst A catalytic material containing CuSAPO was produced. Specifically, copper exchange using 0.2 M copper acetate was carried out on NH4-SAPO-34 at 80°C for 2 hours. The sample was filtered, washed with deionized water, dried at 90°C, and then calcined at 450°C for 2 hours. The resulting CuSAPO-34 had a copper content, expressed as CuO, of 3.3 wt%. The CuSAPO material was evaluated to confirm that stability could be achieved for various types of molecular sieves.

[0157] [Example 7] NOx conversion test NOx conversion was measured in a laboratory reactor at temperatures of 175, 200, 225, 250, 400, 550, and 575 °C in a gas mixture of 500 ppm NO, 500 ppm NH3, 10% O2, 5% H2O, balance N2, under steady-state conditions for 80,000 h. -1 The NOx conversion was measured at gas hourly space velocity versus the volume of the catalyst. NOx conversion was reported as mol% and measured as NO and NO2. CuSAPO of Example 6 and CuCHA of Example 3 were hydrothermally aged at 800°C for 16 hours in the presence of 10% HO / air. Figure 10 shows the NOx conversion of Example 6 versus Example 3. Example 6 shows high NOx conversion in the fresh state and after aging.

[0158] [Example 8] DRIFT spectroscopy for Example 6 DRIFT measurements were performed as described in Example 5. The DRIFT spectrum of the sample of Example 6 is shown in Figure 11. -1 The perturbed TOT bonds in are the Si pairs and the associated Cu 2+ Asymmetric stretching vibration of TOT bond by and Cu(OH) associated with single Si + This is due to the asymmetric stretching vibration of the TOT bond caused by Cu. Peak fitting was again performed in Origin 9.1 software. In peak fitting, the peaks were modeled as Gaussian peaks and the peak fitting was performed until a chi-square tolerance of 1E-6 was reached. As can be seen in Figure 11, the Cu2+ 900 cm, which confirms that ions are associated with Si pairs. -1 The perturbed TOT peak at has the largest area and is the peak at Cu in Example 6. +2 This suggests that was the predominant copper species.

[0159] Hydrothermal aging at 800°C resulted in the 900 and 970 cm peaks for the copper exchanged SAPO-34 molecular sieve of Example 6. -1 This is because the relative TOT peak area in the copper-exchanged SAPO-34 molecular sieve of Example 6 was not changed. +2 and Cu(OH) +1 This also confirms that the relative atomic percentages of do not change with aging, thus demonstrating the high hydrothermal stability of Example 6.

[0160] As shown in FIG. 11 and Table 4, hydrothermal aging at 800° C. reduced the Cu content in Example 6. 2+ and Cu(OH) + The amount of 900 cm for inventive Examples 1 and 6 is not changed, demonstrating the high hydrothermal stability of Example 6. -1 % Peak Area of ​​Peak (A900 cm-1 It can be seen that the 900 cm % for Comparative Example 3 increases by only about 4% upon aging (3 / 71 for Example 1 and 3 / 73 for Example 6). -1 The % peak area of ​​the peak is increased by approximately 77% (33 / 43).

[0161] [Table 4]

Claims

1. A method for identifying a selective catalytic reduction (SCR) catalyst material that is stable to aging during a high temperature hydrothermal condition SCR process, comprising: Cu +2 As cations, and Cu(OH) +1 providing a plurality of samples, each of the samples comprising particles of a copper-containing molecular sieve containing ion-exchanged copper as a cation; Copper-containing molecular sieve Cu +2 The perturbed TOT asymmetric stretching vibration peaks corresponding to the cations and Cu(OH) of the copper-containing molecular sieves +1 subjecting the copper-containing molecular sieve particles to diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy to evaluate the perturbed TOT asymmetric stretching vibration peaks corresponding to the cations; When the copper-containing molecular sieve is fresh, Cu +2 The integrated peak area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is Cu(OH) +1 selecting one or more of the samples that exhibit a ratio of 1 or more to the integrated peak area of ​​the perturbed TOT asymmetric stretching vibration peak corresponding to the cation; The method includes:

2. When the copper-containing molecular sieve is fresh, Cu +2 The percentage of the total integrated peak area attributable to the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is Cu +2 The integrated peak area for the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is expressed as Cu +2 The peak integral area for the perturbed TOT asymmetric stretching vibration peak corresponding to the cation and Cu(OH) +1 The peak integrated area for the perturbed T-O-T asymmetric stretching vibration peak corresponding to the cation is divided by the combined total integrated peak area, and Cu +2 2. The method of claim 1, comprising the step of selecting one or more samples having a percentage of the total peak integrated area attributable to the perturbed TOT asymmetric stretching vibration peak for a cation of 50% or more.

3. 3. The method of claim 2, wherein a plurality of samples are subjected to DRIFT spectroscopy in a fresh state, comprising: Several samples were mixed with 10 mol% H 2 Aging the sample at 800° C. for 16 hours in the presence of air having an O content to form an aged sample; subjecting the aged sample to DRIFT spectroscopy; Cu for one or more samples in the aged state +2 The contribution to the total integrated peak area from the perturbed TOT asymmetric stretching vibration peak corresponding to the cation is calculated as Cu for one or more samples in the fresh state. +2 selecting one or more of the samples that have an increase of 20% or less in the contribution to the total integrated peak area due to the perturbed TOT asymmetric stretching vibration peak corresponding to the cation; The method further comprising:

4. A method for producing a selective catalytic reduction (SCR) catalyst article that is stable to aging during a high temperature hydrothermal condition SCR process, comprising: developing a process for producing a first composition comprising a copper-containing molecular sieve; A sample of the first composition is analyzed in a fresh state using at least DRIFT spectroscopy to determine Cu. +2 and Cu(OH) +1 Based on a comparison of the intensities of the perturbed T-O-T asymmetric stretching peaks corresponding to Cu in the first composition, +2 and Cu(OH) +1 determining the relative amount of Cu +2 selecting a process for commercially producing the first composition if the contribution of the perturbed T-O-T asymmetric stretching peak corresponding to the perturbed T-O-T asymmetric stretching peak to the total integrated peak area of ​​the perturbed T-O-T asymmetric stretching peak is 50% or more; applying a commercially produced first composition made by the process to a substrate to produce a catalytic article; and The method, wherein the total integrated peak area is defined as the sum of the integrated peak area due to the perturbed TOT asymmetric stretching peak corresponding to Cu +2 and the integrated peak area due to the perturbed TOT asymmetric stretching vibration peak corresponding to Cu(OH) +1 .